2021
DOI: 10.1101/2021.06.26.450033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haemosporidian Blood Parasites in nestling birds of prey in Mongolia

Abstract: Haemosporidians are vector-transmitted intracellular parasites that happen in numerous bird species worldwide and may possibly have important effects for wild bird populations. Studies of haemosporidians most dedicated on Europe and North America, and only newly some study in the Neotropics has been done, where the occurrence and influences of the disease have been less considered and are not understood well. In this study we designed a study in the nestling birds of prey in Mongolia. We sampled blood from 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…This association has been reported before in the American kestrel ( Falco sparverius ) during breeding season and coinfected house martins ( Delichon urbicum ) [ 49 , 50 ]. Among hemosporidian parasites, Plasmodium has been linked to mortality and the decline in population levels of native birds in some regions [ 18 ]. Mortality in Strigiformes has been also attributed to coinfections by two or more blood parasite species [ 4 , 20 , 32 , 35 , 37 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association has been reported before in the American kestrel ( Falco sparverius ) during breeding season and coinfected house martins ( Delichon urbicum ) [ 49 , 50 ]. Among hemosporidian parasites, Plasmodium has been linked to mortality and the decline in population levels of native birds in some regions [ 18 ]. Mortality in Strigiformes has been also attributed to coinfections by two or more blood parasite species [ 4 , 20 , 32 , 35 , 37 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Birds of prey are at the top of the food chain and play an important role in maintaining ecological balance [ 15 ]. For that reason, during the past few years, some studies have been published focusing on raptors [ 9 , 16 , 17 , 18 , 19 ]. A thirteen-year study in Beijing revealed that 18% of diurnal raptors tested (Accipitriformes and Falconiformes orders) were positive for blood parasites, in contrast to 38% of nocturnal raptors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%